A Reply to a Note on the Paper “A Simplified Novel Technique for Solving Fully Fuzzy Linear Programming Problems” - Khan, Izaz Ullah; Ahmad, Tahir; Maan, Normah (Journal of optimization theory and applications, 2017)
This note tries to answer issues raised in Bhardwaj and Kumar (J Optim Theory Appl 163(2): 685–696, 2014 ). The research summarizes that the results obtained in Khan et al. (J Optim Theory Appl 159: 536–546, 2013 ) are sound and correct and it fulfills all the necessary requirements of its scope and objectives.